Synthetic aperture radar (Sar) automatic target recognition (atr) using fuzzy co-occurrence matrix texture features - Sansanee Auephanwiriyakul (2018)
© Springer International Publishing Switzerland 2016. Synthetic aperture radar (SAR) image classification is one of the challenging problems because of the difficult characteristics of SAR images. In this chapter, we implement SAR image classification on three military vehicles types, i.e., T72 tank, BMP2 armored personnel carriers (APCs), and BTR70 APCs. The texture features generated from the fuzzy co-occurrence matrix (FCOM) are utilized with the multi-class support vector machine (MSVM) and the radial basis function (RBF) network. Finally, the ensemble average is implemented as a fusion tool as well. The best detection result is at 97.94% correct detection from the fusion of twenty best FCOM with RBF network models (ten best RBF network models at d = 5 and other ten best RBF network models at d = 10). Whereas the best fusion result of FCOM with MSVM is at 95.37% correct classification. This comes from the fusion of ten best MSVM models at d = 5 and other ten best MSVM models at d = 10. As a comparison we also generate features from the gray level co-occurrence matrix (GLCM). This feature set is implemented on the same classifiers. The results from FCOM are better than those from GLCM in all cases.